2002
DOI: 10.1073/pnas.062713399
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirement of bilin chromophore for the photosensory specificity of phytochromes A and B

Abstract: Phytochromes are an important class of chromoproteins that regulate many cellular and developmental responses to light in plants. The model plant species Arabidopsis thaliana possesses five phytochromes, which mediate distinct and overlapping responses to light. Photobiological analyses have established that, under continuous irradiation, phytochrome A is primarily responsible for plant's sensitivity to far-red light, whereas the other phytochromes respond mainly to red light. The present study reports that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Our studies show that it is this blue shift that is responsible for the altered sensitivity of PCYA plants to high-irradiance FRc, rather than an intrinsic difference in the biological activity of the PCB-PHYA adduct compared with native phyA. Indeed, the reduced FRc sensitivity of PCB-treated and PCB analog-treated hy1 and hy2 plants (29) may reflect the same phenomenon.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our studies show that it is this blue shift that is responsible for the altered sensitivity of PCYA plants to high-irradiance FRc, rather than an intrinsic difference in the biological activity of the PCB-PHYA adduct compared with native phyA. Indeed, the reduced FRc sensitivity of PCB-treated and PCB analog-treated hy1 and hy2 plants (29) may reflect the same phenomenon.…”
Section: Discussionmentioning
confidence: 66%
“…Surprisingly, their studies revealed that exogenous PCB and various synthetic PCB analogs rescue most, but not all, of the phytochrome responses in hy1 and hy2 mutant plants. Notable among the responses not restored by PCB feeding was the FR high-irradiance response (FR-HIR), a result implicating the requirement of a P⌽B prosthetic group for this phyA-mediated response (29). Owing to the many mitigating factors that complicate pigment feeding experiments (i.e., poor uptake, optical screening, and solvent͞adjuvant effects, among others), the present study was undertaken to test the effect of chromophore substitution on the photobiological activities of phytochromes in transgenic plants.…”
mentioning
confidence: 99%
“…The highest number of radical amino acid replacements map to the A branch, followed by the NA and NOAC branches ( Figure 3A), and many of these involve changes in charge that may influence proteinchromophore and/or protein-protein interactions. A study of the chromophore requirements of phyA and phyB suggests that tight binding between PHYA and the bilin D-ring may be required for phyA-specific biological activity (Hanzawa et al, 2002). Together, the data suggest that innovation leading to the distinctive spectral sensitivity of phyA and perhaps its lability in light may have occurred after the split of PHYN/A and PHYO/C.…”
Section: Changes On the Na And A Branchesmentioning
confidence: 80%
“…Many of the determinants of functional specificity that distinguish phyA and phyB have been identified from the characterization of monogenic and multiple phytochrome mutants of Arabidopsis, such as those cited above (along with many others), from the dissection of signaling pathways (Castillon et al, 2007;Jiao et al, 2007;Bae and Choi, 2008), and from studies of expression patterns and protein levels (Goosey et al, 1997;Sharrock and Clack, 2002), dimerization (Sharrock and Clack, 2004;Clack et al, 2009), nuclear localization (Kircher et al, 2002), proteinchromophore interactions (Hanzawa et al, 2002), and phyA dark reversion rates (Eichenberg et al, 2000b). Despite these many advances, aspects of the structural-functional models for these photoreceptors remain elusive.…”
Section: Insights From Evolutionary Studiesmentioning
confidence: 99%
“…As mentioned above, we established an efficient and flexible synthetic method of various kinds of bilin chromophores, [46][47][48][49][50][51] including PÈB, 49 PCB, 47,48 and more than 20 kinds of PCB derivatives, 50,51 in free acid forms, which made it possible to assemble them with the apoproteins not only in vitro to analyze the spectral properties of the resulting holoproteins, 125 but also in vivo to observe their physiological functions 126 as will be seen later.…”
mentioning
confidence: 99%